TINJAUAN YURIDIS TERHADAP PERTIMBANGAN HAKIM DALAM PENJATUHAN SANKSI PEMECATAN TERHADAP PRAJURIT TNI DALAM PERKARA ASUSILA - Yunianti, Novi; Syarifuddin, La; Erawaty, Rika (Jurnal Ilmiah Advokasi, 2025)
This study aims to examine the application of dismissal as a criminal sanction against members of the Indonesian National Armed Forces (Tentara Nasional Indonesia), both through court rulings and administrative procedures. In addition, it analyzes judicial considerations in imposing dismissal sanctions in cases of sexual misconduct, particularly in relation to Article 50 of Law Number 48 of 2009 concerning Judicial Power and the imposition of additional punishment in the form of demotion, as reflected in the Military Court Decision of Balikpapan No. 33-K/PM.I-07/AD/VII/2023. This research employs a socio-legal approach to provide a comprehensive understanding of both legal norms and their practical implementation. The findings indicate that dismissal can serve as an alternative sanction, balanced by the imposition of additional punishment in the form of demotion, especially when the defendant has never received disciplinary sanctions in the military. However, the implementation of demotion faces challenges due to the absence of clear procedural regulations, resulting in legal uncertainty in its application. Keywords: Military Criminal Law; Dismissal; Additional Punishment.